The biotechnology business - Daly, Peter (Rowman &​ Allanheld, 1985)
This streamlined version presents a broad, accessible, and comprehensive overview of the business of biotechnology. The elements shaping the industry are defined and explained, enabling you to understand and profit from the expanding influence of biotechnology.